Logging versus fisheries and tourism in Palawan an environmental and economic analysis - Hodgson, Gregor; Dixon, John A. (Honolulu, Hawaii East-West Environment and Policy Institute, 1988)
Occasional paper / East-West Environment and Policy Institute ; no. 7
Keywords: Tourism--Philippines--Palawan.; Fisheries--Philippines--Palawan.; Logging--Environmental aspects--Philippines--Palawan.; Logging--Economic aspects--Philippines--Palawan.